Pemberdayaan Masyarakat Melalui Inovasi Produk Dendeng Ikan Nagari Sungai Nyalo Mudiak Aia - Dara Nur Syakira; Cilmani Hayatul Ulya; Resti Septiani Putri (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Tourism the Mandeh area has experienced rapid growth along with increasing tourist visits, but the community has not yet fully utilized local potential. One of the potentials of Nagari Sungai Nyalo Mudiak Aia is the availability of seafood, particularly fish, which has not been widely processed into value-added products. This article aims to describe community empowerment activities through cooking demonstrations on innovative Dendeng Ikan products as an effort to improve skills and utilize the potential of local fish. The methods used included observation, interviews, and a participatory approach through Focus Group Discussions (FGDs) with PKK women and the local community. The results of the activity showed that participants gained knowledge and skills in processing fish into Dendeng Ikan products, from processing to simple packaging. Active participation and community enthusiasm during the activity indicated that the Dendeng Ikan innovation was readily accepted and had the potential to be developed as a home business. Thus, this activity contributed to increasing the added value of local fishery products and opened up opportunities to increase community income in Nagari Sungai Nyalo Mudiak Aia.